Lumbar Facet Joint Kinematics and Load Effects During Dynamic Lifting. (December 2018) - Chowdhury, Suman K.; Byrne, Ryan M.; Zhou, Yu; Zhang, Xudong
Objective: To examine the lumbar facet joint kinematics in vivo during dynamic lifting and the effects of the load lifted. Background: Although extensive efforts have been dedicated to investigating the risk factors of low back pain (LBP) associated with load handling in the workplace, the biomechanics of lumbar facet joints during such activities is not well understood. Method: Fourteen healthy participants performed a load-lifting task while a dynamic stereo-radiography system captured their lumbar motion continuously. Data from 11 participants were included for subsequent analysis. A randomized block design was employed to study the load effect (4.5 kg, 9.0 kg, and 13.5 kg) on bilateral facet joint motions at approximately 60°, 40°, 20°, and 0° trunk-flexion postures. The facet orientations were also examined. Results: Significant load effects were found for the flexion and lateral bending and superior-inferior translation of the facet joints. The L5-S1 displayed greater lateral bending and twisting, which was due to its more posterolateral orientation than the L2-L3, L3-L4, and L4-L5 facet joints. The left-right asymmetry in facet orientation was observed, most prominently at L3-L4 and L5-S1 facet joints. Conclusion: The lumbar facet joint kinematics are affected by the magnitude of the lifted load and are dependent on the orientations of articulating adjacent facets. Application: This study provided new insights into the role of lumbar facet joints in vivo during lifting. Alterations in the facet joint kinematics due to vigorous functional demand can be one of the primary but overlooked mechanical factors in the causation of LBP.